Three-dimensional model of an ancient Egyptian falcon mummy skeleton. Issue 4 (15th June 2015) - Du Plessis, Anton; Slabbert, Ruhan; Swanepoel, Liani Colette; Els, Johan; Booysen, Gerrie J; Ikram, Salima; Cornelius, Izak
Abstract : Purpose: – The purpose of this paper is to present the first detailed three-dimensional (3D) print from micro-computed tomography data of the skeleton of an ancient Egyptian falcon mummy. Design/methodology/approach: – Radiographic analysis of an ancient Egyptian falcon mummy housed at Iziko Museums of South Africa was performed using non-destructive x-ray micro-computed tomography. A 1:1 physical replica of its skeleton was printed in a polymer material (polyamide) using 3D printing technology. Findings: – The combination of high-resolution computed tomography scanning and rapid prototyping allowed us to create an accurate 1:1 model of a biological object hidden by wrappings. This model can be used to study skeletal features and morphology and also enhance exhibitions hosted within the museum. Originality/value: – This is the first replica of its kind made of an ancient Egyptian falcon mummy skeleton. The combination of computed tomography scanning and 3D printing has the potential to facilitate scientific research and stimulate public interest in Egyptology.